2009
DOI: 10.1530/rep-08-0537
|View full text |Cite
|
Sign up to set email alerts
|

Control of KIT signalling in male germ cells: what can we learn from other systems?

Abstract: The KIT ligand (KITL)/KIT-signalling system is among several pathways known to be essential for fertility. In the postnatal testis, the KIT/KITL interaction is crucial for spermatogonial proliferation, differentiation, survival and subsequent entry into meiosis. Hence, identification of endogenous factors that regulate KIT synthesis is important for understanding the triggers driving germ cell maturation. Although limited information is available regarding local factors in the testicular microenvironment that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 160 publications
1
36
0
Order By: Relevance
“…It has been reported that certain TGF-b superfamily members modulate c-Kit expression in different systems. 35 For other TGF-b family members and antagonists, including activin A, TGF-b1, SB-431542, and Noggin, none of them showed an apparent influence on embryonic c-Kit expression (supplemental Figure 8A-B).…”
Section: Org Frommentioning
confidence: 97%
“…It has been reported that certain TGF-b superfamily members modulate c-Kit expression in different systems. 35 For other TGF-b family members and antagonists, including activin A, TGF-b1, SB-431542, and Noggin, none of them showed an apparent influence on embryonic c-Kit expression (supplemental Figure 8A-B).…”
Section: Org Frommentioning
confidence: 97%
“…The soluble form is initially bound to the cell membrane, but contains an additional 6th exon encoding an extracellular cleavage site. Both forms activate KIT, but with qualitative and quantitative differences [310] [42,310,[312][313][314]. In the embryonic phase the guidance of KIT positive PGCs from the hind gut epithelium to the gonads depends strongly on KITLG mediated chemo attraction [43,313,315,316].…”
Section: Receptor Tyrosine Kinase Signaling: Kit-kitlmentioning
confidence: 99%
“…Both forms activate KIT, but with qualitative and quantitative differences [310] [42,310,[312][313][314]. In the embryonic phase the guidance of KIT positive PGCs from the hind gut epithelium to the gonads depends strongly on KITLG mediated chemo attraction [43,313,315,316]. KIT or KITLG mutant mice show normal establishment of the germ cell lineage in het hind gut, but aberrant proliferation and unsuccessful migration during embryogenesis [42,310].…”
Section: Receptor Tyrosine Kinase Signaling: Kit-kitlmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al, 1992). In addition of their essential role during migration, the interaction of KITLG with its receptor leads to the dimerization of KIT and its auto-phosphorylation activates two major pathways: (1) the PI3K/AKT signaling cascade regulates transcription of mitotic inhibitors such as CDKN1a, CDKN1b and cyclin D1, and enhances the translational factor eIF4E; (2) the MAPK pathway regulates factors involved in pluripotency such as NANOG and SOX2, and in proliferation (Mithraprabhu & Loveland, 2009). By acting on TRP53 activity, KIT/KITLG pathway controls apoptosis of PGCs by regulating the BCL2 components (i.e.…”
Section: Kit and Kitlgmentioning
confidence: 99%